Sequences responsible for the altered erythropoietin responsiveness in spleen focus-forming virus strain SFFVP-infected cells are localized to a 678-base-pair region at the 3' end of the envelope gene. - Chung, S W (1987)
Two different strains of Friend spleen focus-forming virus, SFFVP and SFFVA, are known to cause a rapid erythroleukemia. The SFFVP-infected cells can proliferate and differentiate maximally without the addition of the erythroid-specific hormone erythropoietin, whereas the SFFVA-infected cells require erythropoietin for differentiation and for maximum proliferation. We previously reported that a recombinant virus containing sequences from the 3' half of the SFFVP envelope gene and the SFFVP long terminal repeat on an SFFVA background has all of the biological and biochemical characteristics of SFFVP. We are now presenting data on a new recombinant virus to show that only the 3' half of the SFFVP envelope gene is responsible for the differences observed between the two strains.